International arbitration and the Permanent Court of Arbitration - Indlekofer, Manuel (Alphen aan den Rijn, The Netherlands : Kluwer Law International, 2013)
The modern tendency to restrict international arbitration to matters of commerce and investment is succumbing to a renewed recognition of the original impetus for dispute resolution by arbitration - i.e., matters of public international law, most importantly the settlement of disputes that pose a threat of international conflict. Recent developments suggest a renaissance of public international arbitration, most clearly manifested in the present flourishing of the Permanent Court of Arbitration (PCA), the oldest existing dispute settlement institution in international law. As the calls for the development of new and more appropriate methods for dispute settlement in international law increased during the 1990s, the PCA undertook a structural reform and is today a vital forum for dispute settlement, with scores of arbitrations currently pending under its auspices.--Resume de l'editeur.
Introduction : awakening sleeping beauties? -- Roots of public international arbitration and the Permanent Court of Arbitration -- Public international arbitration in today's dispute settlement framework -- Today's activities of the Permanent Court of Arbitration -- Prospects for international arbitration and the PCA in the twenty-first century -- Conclusion : Institutionalized arbitration revisited.
Includes bibliographical references and index.
Keywords: Permanent Court of Arbitration; Arbitration (International law)